2009
DOI: 10.2166/wh.2009.210
|View full text |Cite
|
Sign up to set email alerts
|

Turbidity and chlorine demand reduction using alum and moringa flocculation before household chlorination in developing countries

Abstract: Over 1.1 billion people in the world lack access to improved drinking water. Diarrhoeal and other waterborne diseases cause an estimated 1.87 million deaths per year. The Safe Water System (SWS) is a household water treatment intervention that reduces diarrhoeal disease incidence among users in developing countries. Turbid waters pose a particular challenge to implementation of SWS programmes; although research shows that a 3.75 mg l 21 sodium hypochlorite dose effectively treats turbid waters, users sometimes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
22
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 17 publications
2
22
0
1
Order By: Relevance
“…Results for protein, ash, dry matter and fibre revealed characteristics similar to those reported by other authors (Akinmutimi, 2006;Kalibbala 2007;Ndyomugyenyi, 2008;Pritchard et al, 2009;Rahman et al, 2009;Sodamade et al, 2013;Olagbemide and Alikwe, 2014). The study of coagulant activity on Moringa (Moringa oleifera), Java plum (Syzygium cumini) and Jackfruit (Artocarpus heterophyllus) revealed promising level of turbidity removal from dirty water that is comparable to previous studies on Moringa and other plant seeds (Kalibbala 2007;Amagloh and Benang, 2009;Preston et al, 2010;Ali et al, 2010;Wilson and Andrews, 2011;Nand et al, 2012;Sanchez-Martin et al, 2012;Kabore et al, 2015). This can be attributed to probable similarity in the turbidity removal agents in the seeds, known to be cationic proteins with pI >9.6 (Ghebremichael et al, 2005).Java plum and Jackfruit seeds demonstrated good protein contents (Table 1) and therefore would be expected to exhibit evident coagulant activity as in Moringa oleifera that was confirmed by this study.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Results for protein, ash, dry matter and fibre revealed characteristics similar to those reported by other authors (Akinmutimi, 2006;Kalibbala 2007;Ndyomugyenyi, 2008;Pritchard et al, 2009;Rahman et al, 2009;Sodamade et al, 2013;Olagbemide and Alikwe, 2014). The study of coagulant activity on Moringa (Moringa oleifera), Java plum (Syzygium cumini) and Jackfruit (Artocarpus heterophyllus) revealed promising level of turbidity removal from dirty water that is comparable to previous studies on Moringa and other plant seeds (Kalibbala 2007;Amagloh and Benang, 2009;Preston et al, 2010;Ali et al, 2010;Wilson and Andrews, 2011;Nand et al, 2012;Sanchez-Martin et al, 2012;Kabore et al, 2015). This can be attributed to probable similarity in the turbidity removal agents in the seeds, known to be cationic proteins with pI >9.6 (Ghebremichael et al, 2005).Java plum and Jackfruit seeds demonstrated good protein contents (Table 1) and therefore would be expected to exhibit evident coagulant activity as in Moringa oleifera that was confirmed by this study.…”
Section: Discussionsupporting
confidence: 81%
“…Microbial removal potential of all the plant seeds extracts was very promising similar to study by Doughari et al (2007) and can deliver water of acceptable quality (WHO, 2011a) for immediate use. It is however known that such treated water contains high organic content that encourages microbial regrowth (Preston et al, 2010;SanchezMartin et al, 2012;Kabore, 2015). Water from such treatment therefore must be consumed immediately if possible and in any case, it should not be drunk after 24 hours.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further research on locally available mechanisms to reduce chlorine demand and turbidity is not indicated in the laboratory setting because this research has already been well established in the literature. 32,33 Targeted research in specific locations where household chlorination is promoted with known high concentrations of THM precursors, such as bromine, is indicated. Bromine presence increases the health risks associated with THMs, as brominated THMs, with higher risk and therefore lower guideline values than chloroform, are formed.…”
Section: Discussionmentioning
confidence: 99%